2018
DOI: 10.1111/tbed.12983
|View full text |Cite
|
Sign up to set email alerts
|

Colostrum transfer of neutralizing antibodies against lumpy skin disease virus from vaccinated cows to their calves

Abstract: The objective of the present study was to access the titres and duration of maternally derived neutralizing antibodies against lumpy skin disease virus (LSDV) in calves born to immunized dairy cows. The study was conducted in a Greek farm of 200 Holstein cows which were immunized with a homologous Neethling strain-based attenuated vaccine. Composite colostrum samples were obtained from 18 selected cows at the day of calving. Blood samples were obtained from each dam-calf pair prior to the first colostrum feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…Similar results were also seen in another study, in which a vaccine containing rotavirus, coronavirus, and Escherichia coli was used to immunise pregnant cattle and led to high titres of specific antibodies in their colostrum and milk [29]. Further, Agianniotaki et al demonstrated the presence of NAs against lumpy skin disease virus until 90 days post-calving [30].…”
Section: Discussionsupporting
confidence: 70%
“…Similar results were also seen in another study, in which a vaccine containing rotavirus, coronavirus, and Escherichia coli was used to immunise pregnant cattle and led to high titres of specific antibodies in their colostrum and milk [29]. Further, Agianniotaki et al demonstrated the presence of NAs against lumpy skin disease virus until 90 days post-calving [30].…”
Section: Discussionsupporting
confidence: 70%
“…Regarding sero-surveillance, the presence of low responders in the vaccinated or naturally infected herds should be considered if the evaluation of the immune status is based solely on serology; positive cattle are protected but negative animals may or may not be protected. Calves born to immunized cows will have a passive immunity that persists for about three to four months [ 76 ]. In 88.9% ( n = 16/18) of calves receiving colostrum from vaccinated dams, neutralizing antibodies were detected in their serum three days after birth.…”
Section: Seroconversion and Duration Of Immunity After Vaccination With Lsd Vaccinesmentioning
confidence: 99%
“…In 88.9% ( n = 16/18) of calves receiving colostrum from vaccinated dams, neutralizing antibodies were detected in their serum three days after birth. The levels of antibodies started to decline with time—after 90 days, only 38.5% ( n = 5) were positive, and after 120 and 150 days, none of the calves had detectable antibodies [ 76 ]. In another study, only in 10% ( n = 3/30) of the calves maternal antibodies were detectable after three months [ 77 ].…”
Section: Seroconversion and Duration Of Immunity After Vaccination With Lsd Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The passive transfer of maternal capripoxvirus antibodies has been investigated by several authors. Agianniotaki et al (2018) [ 86 ] detected antibodies in calves after feeding with colostrum until three months of age, and Milovanovic et al (2019) [ 65 ] showed, through Indirect Fluorescent Antibody Test (IFAT), Virus Neutralization Test (VNT), and Enzyme-linked Immunoassay (ELISA), that cows provide colostral antibodies to their calves. Weiss (1968) also reported the persistence of antibodies in calves after colostrum feeding for up to six months [ 87 ].…”
Section: Immunitymentioning
confidence: 99%